Save yourselves [videorecording (DVD)] - Fischer, Alex H.; Wilson, Eleanor (Motion picture producer and director); Mani, Sunita; Reynolds, John, 1991- (Universal Pictures Home Entertainment, 2020)
A young Brooklyn couple heads to an upstate cabin to unplug from their phones and reconnect with each other. Blissfully unaware of their surroundings, they are left to their own devices as the planet falls under attack.